Application of Deep Learning Algorithm in Cervical Cancer MRI Image Segmentation Based on Wireless Sensor - Liang, Peng; Sun, Guijun; Wei, Sirong (Journal of medical systems, 2019)
With the development of medical technology in China, new difficulties are gradually emerging in traditional medicine. Cervical cancer MRI image segmentation technology based on wireless network is one of the most famous means. But the traditional technology is not strong enough for information processing and analysis. Manual data processing alone may lead to errors in data processing and so on. Therefore, this research was aimed at the MRI image segmentation technology of cervical cancer based on wireless network, using depth learning algorithm to calculate and analyze. Through this kind of wireless network and the computer algorithm form, the data processing ability can be improved and increase the data processing ability be increased.